Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Structural, magnetic, and gas adsorption study of a two-dimensional tetrazole-pyrimidine based metal-organic framework - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2010)
A new two-dimensional (2D) metal-organic framework, Cu-TP-1, has been synthesized under solvothermal conditions (DMF) from the transition metal cation Cu(II) and 2-tetrazole pyrimidine (C5H5N6, H-TP). The structure has been determined by single crystal X-ray crystallography which shows a (6,3) honeycomb 2D net with perpendicular one-dimensional channels. Permanent porosity of Cu-TP-1 has been determined by the nitrogen adsorption isotherm. Cu-TP-1 show interesting H-2 and CO2 uptake. CO2 uptake of Cu-TP-1 (at 298 K, 1 atm pressure) is seen to be comparable to the recently reported ZIF-95 which outperforms ZIF-100 and BPL carbon. The magnetic properties show an antiferromagnetically coupled Cu ... Cu interaction down to 8 K with a Weiss temperature around 108 K.

Solvothermal synthesis, structure, and properties of metal organic framework isomers derived from a partially fluorinated link - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Solvothermal reactions of Cu(NO3)(2) center dot 3H(2)O with 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba) and terminal monodentate ligand 3-methyl pyridine (3-picoline/3-mepy) in the presence of N, N-dimethyl formamide (DMF) and N,N-diethyl formamide (DEF) solvents gave rise to two structurally different two-dimensional (2D) fluorinated metal organic frameworks (F-MOFs). The effect of the choice of solvent has been clearly reflected in the structures obtained. The F-MOFs reported in this paper are formulated as [Cu-2(hfbba)(2)(3-mepy)(2)] center dot (DMF)(2)(3-mepy) (F-MOF-4), [Cu-2(hfbba)(2)(3-mepy)(2)] (Cu-F-MOF-4B), and [Zn-2(hfbba)(2)(3-mepy)(2)] center dot (3-mepy) (Zn-F-MOF-4B) which displays interesting 2D structures with and without interdigitation depending on the solvent used. The structures of these F-MOFs have been determined by X-ray crystallography and further identified by IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). The effect of interdigitation has been reflected in the gas adsorption and magnetic properties of these F-MOFs. These F-MOFs also show comparable H-2 and CO2 uptake depending on their structural variation. Temperature-dependent magnetic susceptibility measurements over a wide range of temperatures exhibit dominantly short-range antiferromagnetic behavior, with weak ferromagnetic behavior showing up at very low temperatures, which is evident from opening of the hysteresis loop with a finite value of coercivity in both F-MOF-4 and Cu-F-MOF-4B. We observed a smaller value of mu(eff) per Cu atom and coercivity in Cu-F-MOF-4B than the F-MOF-4 due to relatively larger distances between the neighboring dicopper paddlewheel secondary building unit.

Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.

Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.

Surface effects on morin transition, exchange bias, and enchanced spin reorientation in chemically synthesized DyFeO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2011)
A giant linear magnetoelectric effect was observed by Y. Tokura's group recently in multiferroic DyFeO3, which demands a detailed investigation of its magnetic properties. Additionally, there is little information on the changes of chemical and physical properties of these materials with the reduction in particle size in spite of the potential applications of these materials nanoscale devices. As the wet-chemical synthesis of these materials in nanosize and getting a control over crystallinity and stoichiometry is nontrivial and poses a serious challenge prohibiting the study of their size-dependent properties. Here, we report the synthesis of DyFeO3 nanoparticles using a surfactantless hydrothermal method with a detailed magnetic property measurement. The as-synthesized DyFeO3 nanoparticles showed excellent crystallinitywith average particle size in the range 50-60 nm. The structural analysis indicated that they are of a distorted orthorhombic pervoslcite crystal structure. Detailed dc magnetization measurements in the temperature range of 3-350 K could isolate the presence of Dy3+-Fe3+ and Dy3+-Dy3+ superexchange interactions, which showed up as spin reorientation transitions in various temperature regions due to the differing magnitude of their interactions resulting in continuous rotation of antiferromagnetic component of Fe3+ spins with cooling of the sample. Nanosized DyFeO3 showed spin-reorientation transitions near 315 and 70K due to the Dy3+-Fe3+ interaction accompanied with an opening up of the hysteresis loop followed by antiferromagnetic ordering around 4 K due to a possible Dy3+-Dy3+ interaction. We also observed significant effect of the particle size reduction on the magnetic properties. The main effects seen. by us were in terms of (1) pronounced spontaneous spin reorientation transitions, (2) the absence of Morin transition, and (3) presence of temperature-dependent exchange bias in the DyFeO3 nanoparticles. We present a detailed mechanism to explain these features based on the interplay of Dy3+ and Fe3+ spins as well surface disorder, anisotropy, canting, and so forth.

Synthesis and optical studies of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Nanoparticle Research, 2011)
{Here we report for the first time, a detailed synthesis mechanism of GdCrO3 nanoparticles using a surfactant-less hydrothermal method. We also report a detailed study of their structural and optical properties. The selected area electron diffraction and powder X-ray diffraction studies of GdCrO3 nanoparticles show pure phase and excellent crystallinity with average particle size around 50-60 nm. The structural analysis indicates a distorted perovskite crystal structure with lattice parameter values of a = 5.3099 +/- A 0.0022
Keywords: hydrothermal; Nanoparticles; Rare earth orthochromites

Solid phase morphological diversity of a rare vanadium cubane (V4O16) based metal organic framework - Dey, Chandan; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2012)
A Cu(II) connected V4O16-cubane based metal organic framework, Cu-2(phen)(2)(V4O8) (PO4)(4) [Cu2V4O16-2D] was synthesized under hydrothermal conditions. This is the first example of transition metal connected V4O16-cubane based MOF. X-ray single crystal data shows the alternate arrangement V4O16-cubane and Cu(phen)(O)(3) square pyramidal unit in two dimensions. These two-dimensional sheets are stacked on top of each other to form a three-dimensional architecture. Cu2V4O16-2D shows two types of solid state morphologies of the same phase, which was confirmed by scanning electron microscopy. It is noteworthy that this type of morphological difference of the solid phase in an extended metal organic hybrid material is rare and has not been perceived in the polyoxovanadate based MOFs literature. Cu2V4O16-2D was further characterized by powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), IR-spectroscopy, scanning electron microscopy (SEM), and elemental analysis. We also studied the static magnetic and gas adsorption properties for Cu2V4O16-2D.

Synthesis, characterization, and magnetic studies of coordination polymers with Co(II) and Mn(II) ions - Ahmad, Musheer; Das, Raja; Lama, Prem; Poddar, Pankaj; Bharadwaj, Parimal K. (Crystal Growth & Design, 2012)
{An ether bridged tricarboxylic acid ligand, 5-(4-carboxybenzyloxy)isophthalic acid (p-cbiaH(3)) has been used to construct three coordination polymers with Co(II) salts in presence of different nitrogen donor ligands such as 1,4-bis(4-pyridinylmethyl)piperazine (bpmp), dipyridine-4-yl-diazene (dpd), and 4,4'-bipyridine (bpy). The products formed under hydrothermal conditions are formulated as {[Co-3(p-cbia)(2)(bpmp)(2)(H2O)(6)]center dot 10H(2)O}(n) (1), {[Co-2(p-cbiaH)(2)(dpd)(H2O)(2)]\

Static and dynamic magnetic properties and effect of surface chemistry on the morphology and crystallinity of DyCrO3 nanoplatelets - Gupta, Preeti; Bhargava, Richa; Das, Raja; Poddar, Pankaj (RSC Advances, 2013)
In this contribution, the structural and magnetic properties of DyCrO3 nanoplatelets, synthesized by a hydrolytic sol-gel method, have been investigated. The crystalline phase of DyCrO3 was attained at the decomposition temperature of 800 degrees C for citric acid and oxalic acid, respectively and their structural analysis indicates a distorted orthorhombic perovskite structure of the DyCrO3 nanoplatelets. The dc-magnetization curve shows the Neel temperature of similar to 144 and similar to 146 K for DyCrO3 nanoplatelets synthesized using citric acid (DCO (C)) and oxalic acid (DCO (O)), respectively. In addition, DCO (O) shows weak anomalies at similar to 22 and similar to 6 K in the zero-field-cooled and field-cooled magnetization curves. Below the Neel temperature, DCO (C) and DCO (O) exhibit cross-over from positive to negative magnetization at similar to 143 and similar to 145 K, respectively. This was attributed to a Dy3+-Cr3+ interaction, which resulted in a weak ferromagnetic coupling (seen as a small opening in the M-H curves). The low temperature transition observed at similar to 6 K can be assigned to the onset of Dy3+-Dy3+ antiferromagnetic interaction.

Static and dynamic magnetic properties and interplay of Dy3+, Gd3+ and Mn3+ spins in orthorhombic DyMnO3 and GdMnO3 nanoparticles - Das, Raja; Jaiswal, Adhish; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2013)
Single-phase orthorhombic DyMnO3 and GdMnO3 nanoparticles in the size range 60-70 and 35-45 nm, respectively, were synthesized using a modified hydrothermal method. The magnetic property measurements of DyMnO3 nanocrystals show anomalies around similar to 43K (antiferromagnetic (AFM) coupling between Mn3+ spins) and at 7K in the form of a peak in the zero-field-cooled curve (AFM coupling between Dy3+ spins). Whereas, GdMnO3 undergoes a phase transition at similar to 42K from paramagnetic to an incommensurate-antiferromagnetic phase (ICAFM) followed by a second anomaly at similar to 22 K, which could be associated with the transition from ICAFM into a canted A-type AFM ordering of the Mn3+ spins. This transition is followed by a long-range ordering of the Gd3+ moments at 6K yielding the canting of the Gd3+ spins with a ferromagnetic (FM) component antiparallel to the FM moment of the canted Mn3+ spins. No anomaly near the Neel temperature of the Mn moments for both DyMnO3 and GdMnO3 nanoparticles was observed in ac magnetization which were observed in dc magnetization. The room temperature Raman spectra of DyMnO3 shows two most intense Raman modes at 480 and 609 cm(-1) which can be assigned to an antisymmetric Jahn-Teller stretching mode and a symmetric or breathing stretching mode, respectively, involving Mn-O bond stretching.

Surface chemistry and growth mechanism of highly oriented, single crystalline TiO2 nanorods on transparent conducting oxide coated glass substrates - Sadhu, Subha; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (RSC Advances, 2013)
The fabrication of one-dimensional (1D) rods or wires of titania in desired crystalline facets is quite exciting due to unique optoelectronic properties. The single crystalline, oriented nanorods directly grown on transparent conducting oxide (TCO) substrates are finding a lot of interest in solar photovoltaics and several other optoelectronic devices due to enhanced electron transport and lower exciton recombination rates. However, the growth of desired crystalline facets of highly oriented, single crystalline nanorods on different substrates and understanding the interplay between the surface chemistry and growth mechanism still remain a non-trivial and challenging task. Here, for the first time, the kinetically controlled growth of the (310) facet of TiO2 nanorods on fluorine-doped tin oxide (FTO) coated glass substrate has been reported which is in contrast to the previously reported (002) faceted TiO2 nanorods. In addition to this, the growth of (110) facet TiO2 nanorods using amorphous fluorine doped silicon oxide (FSO) as a substrate is also demonstrated. In this paper, it is shown that two different faceted TiO2 nanorods can be synthesized following same synthetic condition by varying only the material properties of the substrate. To investigate the role of substrate chemistry on the morphology and single crystallinity of TiO2 nanorods, electron microscopy, XPS and contact angle measurements have been done. The results clearly indicate an important link between the surface chemistry and morphology of TiO2 nanorods. It can be assumed that there is a role of OH- and water groups which are responsible for the growth of plane (110) which has less surface energy. The observation of (310) facet is quite surprising and can be explained based on FTO crystallinity. It is possible to tune the diameter of the titania nanorods by further coating the FTO substrate with a thin gold layer due to increase in the hydrophilicity of the substrate. Finally, a light to electricity conversion efficiency of 2.5% could be achieved by using vertically grown titania nanorods on FTO as the photoanode in a dye sensitized solar cell (DSSC).

Static and dynamic photoluminescence and photocatalytic properties of uniform, monodispersed up/down-converting, highly luminescent, lanthanide-ion-doped beta-NaYF4 phosphor microcrystals with controlled multiform morphologies - Padhye, Preeti; Poddar, Pankaj (Journal of Materials Chemistry A, 2014)
Lanthanide-ion-doped, single-crystalline hexagonal phase NaYF4 microcrystals with multiform morphologies, such as microrods, hexagonal microprisms, and spindle-like structures, were fabricated via a cationic/anionic binary capping agent system: CTAB and a tri-sodium citrate-assisted hydrothermal route. The influence of synthesis conditions on the crystalline morphology was studied and the possible growth mechanisms are presented systematically. The down-conversion and up-conversion photoluminescence (PL) properties of beta-NaYF4:Ln(3+) (Ln = Tb, Yb/Er, and Yb/Tm) were investigated. The static and dynamic PL studies of beta-NaYF4:5% Tb3+ showed strong dependence of luminescent properties on the crystalline morphology. Furthermore, the beta-NaYF4:5% Tb3+ phosphors exhibited efficient photocatalytic activity under UV as well as solar light irradiation, and showed enhanced selectivity towards methylene blue. Moreover, the morphological effect on the photocatalytic activity of beta-NaYF4:5% Tb3+ crystals has also been studied. The high luminescence efficiency and strong photocatalytic activity of beta-NaYF4:5% Tb3+ make them a potential phosphor material and promise to provide a gateway into other applications as in biology and materials sciences.

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices

Study of the nucleation and growth of antibiotic labeled Au NPs and blue luminescent Au-8 quantum clusters for Hg2+ ion sensing, cellular imaging and antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report a detailed experimental study supported by DFT calculations to understand the mechanism behind the synthesis of cefradine (CFD - an antibiotic) labeled gold nanoparticles (Au NPs) by employing CFD as both a mild reducing and capping agent. The analysis of the effect of growth conditions reveals that a higher concentration of HAuCl4 results in the formation of an increasing fraction of anisotropic structures, higher temperature leads to the formation of quasi-spherical particles instead of anisotropic ones, and larger pH leads to the formation of much smaller particles. The cyclic voltammetry (CV) results show that when the pH of the reaction medium increases from 4 to 6, the reduction potential of CFD increases which leads to the synthesis of nanoparticles (in a pH 4 reaction) to quantum clusters (in a pH 6 reaction). The MALDI-TOF mass spectrometry results of supernatant of the pH 6 reaction indicate the formation of [Au-8(CFD)(2)S-6] QCs which show fluorescence at ca. 432 nm with a Stokes shift of ca. 95 nm. The blue luminescence from Au-8 QCs was applied for sensing of Hg2+ ions on the basis of an aggregation-induced fluorescence quenching mechanism and offers good selectivity and a high sensitivity with a limit of detection ca. 2 nM which is lower than the detection requirement of 10 nM by the U.S. EPA and 30 nM by WHO for drinking water. We have also applied the sensing probe to detect Hg2+ ions in bacterial samples. Further, we have investigated the antibacterial property of as-synthesized Au NPs using MIC, growth curve and cell survival assay. The results show that Au NPs could reduce the cell survival very efficiently rather than the cell growth in comparison to the antibiotic itself. The scanning electron microscopy study shows the degradation and blebbing of the bacterial cell wall upon exposure with Au NPs which was further supported by fluorescence microscopy results. These Au NPs did not show reactive oxygen species generation. We believe that the bacterial cytotoxicity is due to the direct contact of the Au NPs with bacterial cells.

Study of magnetic and thermal properties of SmCrO3 polycrystallites - Gupta, Preeti; Poddar, Pankaj (RSC Advances, 2016)
In the present work, we have studied the magnetic and thermal properties of sol gel derived samarium chromite (SCO) polycrystallites. The magnetic measurements of SCO polycrystallites show a characteristic antiferromagnetic transition T-N similar to 190 K and spin reorientation temperature T-SR similar to 33 K, which is in the region of interest to study a possible magnetocaloric effect (MCE). The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. The SCO polycrystallites possesses both inverse (positive) and normal (negative) MCE at and above around the spin reorientation transition (TSR) with Delta S-M(max) M values of similar to -24 x 10(-2) & 13 x 10(-2) J kg(-1) K-1, respectively. The SCO also shows another normal (negative) MCE peak around its Neel transition (T-N) with -Delta S-M(max) M similar to 11 x 10(-2) J kg(-1) K-1. The presence of two successive MCE peaks in SCO in the temperature range of 3-50 K, leads to an similar to 47 K operating temperature window with one thermodynamic cycle. In addition, the low temperature heat capacity (C-P) measurements of SCO polycrystallites reveal a lambda-shaped peak at T-N which is associated with a conventional second- order, paramagnetic to antiferromagnetic (AFM), phase transition. The temperature and magnetic field dependence of the specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). In addition the C-P vs. T curve in SCO also shows a weak anomaly around the similar to T-SR along with a Schottky anomaly below 10 K.

Study of magnetic entropy and heat capacity in ferrimagnetic Fe3Se4 nanorods - Sen Bishwas, Mousumi; Poddar, Pankaj (Journal Of Physics D-Applied Physics, 2016)
Change in the magnetic entropy and specific heat capacity in Fe3Se4 nanorods synthesized by a wet-chemical method in a broad temperature (215-340 K) and magnetic field range (0-60 k Oe) was studied. The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. S-M(max) of -46 x 10(-2) J kg(-1).K-1 was obtained at similar to 317 K when the field was changed from 0 to 60 kOe. The maximum in the isothermal magnetic entropy change (Delta S-M) is observed in close proximity to TC (similar to 323 K), which is linked to the order-disorder transition. The nature of this transition was analyzed by universal curve behavior. The temperature and magnetic field dependence of specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). The magnetic entropy change of Fe3Se4 nanoparticles is found to be comparable with similar ferrite and manganite nanoparticle systems and a broad operating temperature window of similar to 30 K was observed around room temperature.
Keywords: heat capacity; iron selenide; Magnetic anisotropy; magnetic entropy; order-disorder phase transition

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Study of the phase-evolution mechanism of an Fe-Se system at the nanoscale: optimization of synthesis conditions for the isolation of pure phases and their controlled growth - Ghalawat, Monika; Poddar, Pankaj (Langmuir, 2020)
The iron selenide (Fe-Se) family of nanoparticles (FexSey-where x/y ranges from 1:2 to 1:1) has been fabricated by a thermal decomposition method. The control over solution chemistry has been developed by intensively investigating the effect of reaction parameters by means of wide-angle X-ray scattering, leading to the rich insights into the phase-evolution mechanism of the Fe-Se system. The phase transformation followed the FeSe2 -> Fe3Se4 -> Fe7Se8 -> FeSe sequence in the temperature range of 110-300 degrees C. The deep mechanistic insight helped in the identification of optimized conditions needed to crystallize the individual phase of the Fe-Se system as well as control of the morphology, crystalline phase purity, and thermal stability of the obtained Fe-Se nanoparticles.

Study of growth kinetics of Fe3Se4 nanocrystallites and the influence of size and shape tunability on their magnetic properties - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2021)
Crystalline iron selenide (Fe3Se4) nanoparticles (NPs) present a useful model system for a fundamental understanding of magnetism apart from having potential applications in permanent-magnet-related technologies. Despite significant advancements in understanding of the nucleation and growth processes, control over size and shape tunability is nontrivial, especially for the transition metal chalcogenides (TMC). The Wulff theorem states that if a crystal can grow purely under thermodynamic control of parameters then it will adopt the shape determined by the surface-energy minimization, i.e., the surface energy minimization will drive the growth of each crystalline facet. However, the known or unknown, controllable or uncontrollable parameters of a typical reaction which makes kinetic growth more art than science, depending upon whether we understand them or not. There is hardly any study based on existing models and theories to explain the TMC morphology evolution. In this work, there is a conscious effort to know, understand, and control the individual role of various reaction pathways on the shape and size of the Fe3Se4 nanocrystals. A qualitative growth mechanism is proposed based on the diffusion and reaction processes. Furthermore, the influence of shape/size on the magnetic parameters such as coercivity (H-C), magnetization (M-60kOe), effective magnetic anisotropy constant (K-eff), energy product (BHmax), and average blocking temperature (T-B) is investigated for Fe3Se4 NPs. After diving deeper into the science of crystal growth, our insight provides valuable guidance on experimental conditions for the synthesis of Fe3Se4 NPs with tunable sizes/shapes which for the first time can be extended to most TMCs.

Scalable synthesis of dodecanethiol-capped bismuth nanoparticles by a solvent-free solid-state grinding method for reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (Langmuir, 2023)
Thiol-capped metal nanoparticles have two constituents:an inorganicmetal and an organic molecule as a shell. Both characters are inbuiltin the structure of the metal thiolate. Herein, we have investigatedbismuth dodecanethiolate as a precursor for the synthesis of dodecanethiol-cappedbismuth nanoparticles (Bi NPs) by a solid-state grinding method. Byusing sodium borohydride and bismuth dodecanethiolate, crystallinebismuth nanoparticles are synthesized in a solvent-free environmentat room temperature (24 & PLUSMN; 4 & DEG;C). Bi NPs are tested for catalyticactivity by reducing 4-nitrophenol (4-NP) to 4-aminophenol (4-AP)with an excess of NaBH4. Dodecanethiol-capped bismuth nanoparticlesexhibit an efficient reduction of 4-NP to 4-AP within 12 min. Additionally,these nanoparticles remain catalytically active for up to three cycles.

Self-powered wearable breath sensor cum nanogenerator using AuNR-rGO-PVDF nanocomposite - Bang, Amruta D.; Ghalawat, Monika; Poddar, Pankaj; Kulkarni, Sulabha K.; Adhyapak, Parag V. (IEEE Sensors Journal, 2023)
Breathing is the most important function of living being. It is well known that breath contains 90% humidity along with various gases and volatile organic compounds (VOCs). These gases are released during various metabolic activities in the body. These gases present in the breath can act as biomarkers to showcase healthiness or abnormalities in the body. Therefore, breath sensors are the need of time to detect diseases at early stages and in noninvasive way. Herein, we report, simple breath sensor using Au nanorods (AuNRs) and its nanocomposite with reduced graphene oxide (rGO) and polyvinylidene fluoride (PVDF). The nanocomposites system is designed in such a way that each component has its advantages for breath sensing. Here, AuNR being a good humidity sensitive material detects the breath efficiently. The ss phased PVDF being a very good ferroelectric material, contributes for voltage generation during sensing and enables the device to be self powered. The highly conducting rGO increases the sensitivity and voltage generation by facilitating the electron transport in the nanocomposite system. The nanocomposite was optimized with respect to PVDF, rGO and Au concentration. The as-synthesized materials were characterized by physiochemical characterization techniques such as field emission scanning electron microscopy (FESEM), X-ray diffraction analysis (XRD), UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The ss phase formation of the PVDF was confirmed from the XRD peak at 20.41 degrees. SEM results revealed that AuNR have length 15-20 nm and aspect ratio similar to 3-4. Breath sensing tests were carried out for as synthesized nanocomposite material. The nanocomposite exhibited high sensitivity towards breath and generated the voltage of similar to 0.7 V within 0.8 s.
Keywords: Au nanorods (AuNRs); breath analyzer; breath sensor; nanogenerator

Systematic study of rare-earth ions size-dependent structural phase transition from monazite to zircon-type in rare earth chromates using Raman spectroscopy - Ughade, Supriya; Poddar, Pankaj (Journal of Raman Spectroscopy, 2023)
Rare earth chromates (RCrO4) undergo monazite to zircon-type structural phase transition due to a decreased rare-earth ion size. They also exhibit an intermediate mixed phase. However, there is no systematic study on the influence of structural distortion on their phononic behavior, which is quite sensitive to subtle environmental variations. A change in the room temperature phononic spectrum was studied in the family of RCrO4 compounds, where R was varied from La to Yb using Raman modes. With an increase in the atomic number from Nd to Yb for zircon-type phases, the external translational and rotational modes were observed to shift towards lower and higher wavenumbers, respectively. At the same time, all internal vibrational modes shifted towards higher phonon energies. A comparison between Raman modes for monazite, intermediate, and zircon-type RCrO4 phases showed a gradual shift in the internal modes towards a higher wavenumber. The confirmation of the change in Raman modes with the decreasing radius was found by comparing the rare-earth elements in DyCrO4 and LaCrO4 with non-rare-earth elements in YCrO4.
Keywords: monazite-type; Raman spectroscopy; rare earth chromates (RCrO4); YCrO4; zircon type

Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite